LB1.69 Clinical and analytical evaluation of the new aptima mycoplasma genitalium assay on the panther instrument (HOLOGIC), m. genitalium prevalence, and antimicrobial resistance in m. genitalium in sweden, denmark and norway in 2016. (8th July 2017) - Unemo, Magnus; Salado-Rasmussen, Kirsten; Hansen, Marit; Olsen, Anne Olaug; Falk, My; Golparian, Daniel; Ringlander, Johan; Nilsson, Christian Steczkó; Moi, Harald; Westh, Henrik; Jensen, Jörgen Skov
Abstract : Introduction: Mycoplasma genitalium (MG) is a frequent aetiology of urethritis and cervicitis, which can result in severe reproductive complications. Resistance in MG to first-line (azithromycin) and second-line (moxifloxacin) treatment has rapidly increased. The new CE-marked APTIMA MG assay (Hologic) is now commercially available. Our aims were to evaluate the clinical and analytical sensitivity and specificity of the new APTIMA MG assay and an APTIMA MG RUO assay, and describe the prevalence of MG, N. gonorrhoeae, C. trachomatis and resistance to azithromycin and moxifloxacin in Sweden, Denmark and Norway in 2016. Methods: From January 2016 to March 2017, first-void urine (from males) and vaginal swabs were collected from consecutive attendees at 3 STD clinics in Sweden, Denmark and Norway. All samples were tested with the APTIMA MG assay, APTIMA MG RUO assay, APTIMA CT/NG assay, and a quantitative mgpB PCR. Resistance was determined by sequencing of the 23S rRNA gene and parC . For analytical evaluation, isolates of diverse genome-sequenced MG and other mycoplasma species in different concentration were tested. Results: In total, 5269 patients were included. The rate of MG infected patients was 7.3%, however, the rate significantly varied in the different countries. The sensitivity of the APTIMA MG assay, APTIMA MG RUO assay and mgpB PCR ranged between 95.8%–100%, 95.8%–100%, and 73.2%–81.6%, respectively, in the countries. The specificity of the APTIMA MG assay, APTIMA MG RUO assay and mgpB PCR ranged between 99.6%–100%, 100%, and 99.7%–100%, respectively. The resistance level to azithromycin was 40% (18%–56% in the countries) and multidrug resistance (to both azithromycin and moxifloxacin) was found in all countries. Conclusion: Both the APTIMA MG assays had a significantly superior sensitivity compared to the mgpB PCR. The prevalence of MG as well as azithromycin resistance was high. Increased testing using validated and quality assured molecular tests for MG, antimicrobial resistance surveillance and routine resistance testing in MG-positive samples is crucial.